Social Media Portfolio: Crunchy Dory / Izzat Naseer Md Fauzi - Md Fauzi, Izzat Naseer (2020)
Crunchy Dory is a trademark of our Dory Skin Salted Egg which is located in Johor Bahru, Johor. The key aim to achieve for the company is to earn more income and produce more revenue to keep our product increasing and expanding financially. They also give our customers high degree of satisfaction by offering the best quality. Our businees began on November 23th, 2020. Our product has given a fantastic taste based on the customer review, because the tangy of making our customer remember the taste. Despite of the reasonable and affordable price, the product is likely accepted by many people. Therefore, it gives a strong perspective to continue selling to our customers. Because of our concerns to recognize rural residents, our business plans to create a strong market place in town. Since its opening early, more than 50 bottles were sold. Increasing demands for our product results in our business project having a good profitable sales revenue. Hence, it is a good marketable product of choice that can be extended further into many different areas as the company continues to grow. We believe this is one of our products which can strengthen our market business. Our business’s vision is to be one of the future’s retailer business in Johor Bahru and also implement a high-quality product through an innovation that enable us to be success in the future. While our mission is to provide tasty food, unique product and friendly service within the community to satisfy our customer’s need and want. The future expectation of the business is we want to be well-known retailer (Dory Skin) in food industry. We also want to enlarge our target market location to whole Malaysia. Other than that, we want to utilize our resources and inventories in the same time maximize our profit. As our business is still small, in future we want to expand the business by having several runners in Johor Bahru. We strongly believe that there are many significant opportunities that we can do to the further expansion. We intend to strengthen our sale and distribution network by enlisting experienced marketing and sales personal.